Failure to find a distance effect in pigeon choice. Issue 1 (24th May 2017) - Bell, Matthew C.; Sanabria, Federico
Abstract : Primates take longer to choose between alternatives with smaller differences in value. This effect—a particular instance of the distance effect in symbolic comparisons—has not been replicated in birds. Instead, birds appear to respond independently to each alternative, such that the latency to choose depends primarily on the alternative of highest value. Three experiments tested for the distance effect in pigeons under conditions not previously considered. Experiment 1 presented pigeons with forced‐ and binary free‐choice trials, where each alternative was one of three possible delays to reinforcement (4, 8, and 16 s). Pigeons were exposed to the choice stimuli for different amounts of time and with different sample response requirements prior to the choice response. Experiment 2 added a fourth (0‐s delay) alternative. Experiment 3 substituted the 16‐s delay with a second 4‐s delay. In all experiments, pigeons systematically chose the shortest delay to reinforcement. Latency to choose the 4‐s delay did not vary when choosing against the 8‐s or 16‐s delay, regardless of whether choice stimuli were exposed for the duration of nine pecks (Experiment 1), or whether a 0‐s delay alternative was sometimes present (Experiment 2). Latency to choose the preferred of two identical alternatives (4‐s vs. 4‐s) was shorter than the latency to choose between different alternatives (4‐s vs. 8‐s; Experiment 3); this is the opposite of a distance effect. These results show no evidence of a distance effect in pigeon choice, consistent with the hypothesis that pigeons respond independently to each choice alternative.